Pengaruh kompetensi sosial guru, keterlibatan keluarga, dan gaya belajar terhadap prestasi belajar siswa dengan motivasi belajar sebagai variabel moderasi di SMK Widya Praja Ungaran - Rahmat, Irfandah; Miftahunnajah, Nimas Aulia Pambajeng (Jurnal Pendidikan Ekonomi (JUPE), 2026)
This study aims to analyze the influence of teachers’ social competence, family involvement, and learning styles on students’ academic achievement, with learning motivation as a moderating at SMK Widya Praja Ungaran. The study employed an explanatory quantitative approach with 70 respondents. Analysis (MRA) with the assistance of SPSS 26. The results revealed that: 1) teachers’ social competence has a positive and significant effect on academic achievement; 2) family involvement has a negative and insignificant effect on academic achievement; 3) learning styles have a positive and significant effect on academic achievement; and 4) learning motivation moderates the influence of teachers’ social competence and learning styles on academic achievement but does not moderated the relationship between family involvement and academic achievement.